Role of advanced magnetic resonance imaging techniques in the evaluation of glioblastoma multiforme - Rashid, Mehzabin Binte; Akter, Rashida; Raut, Arpita; Afrin, Orin; Sakhawat Hossain, M. M. (International Journal of Research in Medical Sciences, 2025)
Background: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor in adults, often presenting with nonspecific clinical and radiological features that complicate early diagnosis. Advanced magnetic resonance imaging (MRI) techniques, including diffusion-weighted imaging (DWI), gradient-echo (GRE) sequences and magnetic resonance spectroscopy (MRS), may enhance diagnostic accuracy beyond conventional MRI. Methods: This cross-sectional study was conducted in the Department of Radiology and Imaging, Sir Salimullah Medical College and Mitford Hospital, Dhaka, in collaboration with Neurosurgery and Pathology departments, from January 2018 to December 2019. A total of 31 patients with clinically suspected GBM were enrolled using purposive sampling. All patients underwent advanced MRI protocols, including DWI, GRE and MRS. MRI findings were compared with histopathological diagnoses, considered the gold standard. Results: The mean patient age was 52.1±11.2 years, with most cases (41.9%) in the 51–60-year group. On DWI, partially restricted diffusion was observed in 51.6% of lesions, particularly among GBM cases (54.1%). Blooming artifacts on GRE were seen in 41.9% overall, including 37.5% of GBM. MRS consistently showed elevated choline, lactate and choline/creatinine ratio with reduced NAA and creatinine. A choline/creatinine ratio >2.5 distinguished GBM and anaplastic astrocytoma, while metastases showed ratios <2.5. Compared with histopathology, MRI achieved a sensitivity of 95.6%, specificity 75.0%, accuracy 90.3%, PPV 91.6% and NPV 85.7%. Conclusion: Advanced MRI techniques provide significant diagnostic value in differentiating GBM from other intracranial tumors, with high sensitivity and accuracy when correlated with histopathology.